MIKROANATOMI HEPAR MENCIT (Mus musculus) SETELAH PEMBERIAN KITIN PER-ORAL - Isdadiyanto, Sri (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT--The  objective of  the experiment  was determines  liver  microanatomy  and diet consumption  n  the Mus muscalus  after give of  chitin. This research  used  completely  randomized  design. There  were  fow  concentration  of chitin, 0 mg chitin per day; 1,3 mg chitin per day; 1,95  mg chitin per day; 2,6 mg chitin per day. Anova  was  used  in data  analysis  and  LSDT test  in 57o  level. The  result  of experiment indicated  that  the  chitin was  not cause alteration  on  liver microanatomy.Keywords:  chittin, Mus musculus, liver microanatomy